Environmental drivers of benthic community structure in a deep sub-arctic fjord system. (30th September 2019) - Jordà Molina, Èric; Silberberger, Marc J.; Kokarev, Valentin; Reiss, Henning
Abstract: Fjords are unique geomorphological features that are found globally along (previously) glaciated coasts. They are characteristic for the entire Norwegian coast, where growing human populations and economic development increasingly impact the associated fjord ecosystems, and accordingly basic knowledge about ecosystem structure and functioning is needed. Knowledge about benthic systems within deep basins (over 400 m) of sub-Arctic fjords is currently missing and it remains questionable whether our understanding of similarly deep temperate fjords or shallower sub-arctic fjords is directly transferable to such systems. This study aims to investigate the patterns of soft-bottom benthic communities within a northern Norwegian deep multibasin fjord system and relate them to the prevailing environmental conditions, following a sampling strategy of many-sites with one-sample each. Here we show that oxygen content of the water and organic matter gradients in the sediment, structure the benthic communities of the fjord reflecting the main basins. We found that the community of the deepest basin (>700 m) of this sub-Arctic fjord is similar to the community just outside of Tysfjord at the same depth but differ from other communities within the fjord. Furthermore, the deep basin community reflects deep communities of temperate fjords and the deep Skagerrak. The community within the innermost basin is well adapted to periodic hypoxia with low quality or degraded food supply. Our results demonstrated that fjord specific multibasin topography and the corresponding environmental factors are important drivers of ecological processes, which resulted in distinct benthic communities in each of the three basins. The management of such heterogeneous fjord ecosystems should take an adaptive approach and apply measures that take the differences of these benthic communities into account. Highlights: Benthic community structure in Tysfjord reflects the main basins. Samples from the deepest basin are species poor and dominated by few taxa. O2 deficiency in a basin with shallow sill is a key driver of community structure. Organic enrichment in the basins can explain the depth related community structure.